Proteomic analysis of peripheral nerve myelin during murine aging - Helbing, Dario Lucas; Kirkpatrick, Joanna M.; Reuter, Michael; Bischoff, Julia; Stockdale, Amy; Carlstedt, Annemarie; Cirri, Emilio; Bauer, Reinhard; Morrison, Helen (Frontiers in Cellular Neuroscience, 2023)
Aging of the peripheral nervous system (PNS) is associated with structural and functional changes that lead to a reduction in regenerative capacity and the development of age-related peripheral neuropathy.Myelin is central to maintaining physiological peripheral nerve function and differences in myelin maintenance, degradation, formation and clearance have been suggested to contribute to age-related PNS changes. Recent proteomic studies have elucidated the complex composition of the total myelin proteome in health and its changes in neuropathy models. However, changes in the myelin proteome of peripheral nerves during aging have not been investigated. Here we show that the proteomes of myelin fractions isolated from young and old nerves show only subtle changes. In particular, we found that the three most abundant peripheral myelin proteins (MPZ, MBP and PRX) do not change in old myelin fractions. We also show a tendency for high-abundance myelin proteins other than these three to be downregulated, with only a small number of ribosome-related proteins significantly downregulated and extracellular matrix proteins such as collagens upregulated. In addition, we illustrate that the peripheral nerve myelin proteome reported in this study is suitable for assessing myelin degradation and renewal during peripheral nerve degeneration and regeneration. Our results suggest that the peripheral nerve myelin proteome is relatively stable and undergoes only subtle changes in composition during mouse aging. We proffer the resultant dataset as a resource and starting point for future studies aimed at investigating peripheral nerve myelin during aging. Said datasets are available in the PRIDE archive under the identifier PXD040719 (aging myelin proteome) and PXD041026 (sciatic nerve injury proteome).